Begravelser på en katedralkirkegård: Hamar domkirkeruin - Sellevold, Berit J. (Hikuin, 2000)
Burials in a cathedral churchyard: The Hamar cathedral ruin By Berit J. Sellevold Archaeological excavations during the 1990’s around the medieval cathedral ruin at Hamar in Southeast Norway have brought forth skeletal remains of c. 1200 individuals: c. 600 from undisturbed graves and c. 600 in the assemblage of dispersed bones from disturbed graves. Analyses of the skeletal remains show that the cathedral cemetery was a high status churchyard used by the ecclesiastical community of Hamar. The age and sex distributions in the material differ from the expected distributions of a parish churchyard: 3/4 of the sex determined individuals were men, most of whom had died in young adult age and middle age. The age profile of the buried female population was different: most females had died in middle age and old age, and there were few young adult females. More than 1/4 of the males had statures over 180 cm. The distribution of, i.a., tall individuals in the churchyard points to status as a determining factor with regard to the location of graves, suggesting an adherence to the regulations given in the medieval provincial laws. The results of the analyses of the Hamar cathedral cemetery and skeletal remains clearly demonstrate that demographic data from medieval churchyards do not provide information about medieval society in general. The data only applies to the particular sector of society which is represented in the buried population in a given cemetery.